Artificial Intelligence and Money Laundering in The Application of International Criminal Law - Miguel Abel (Generate Digital Publishing, 2026)
Objective: This study examines the legal and theoretical issues related to using Artificial Intelligence (AI) for preventing and enforcing money laundering under international and European law. It highlights the conflict between technological advancements and the safeguarding of fundamental rights, especially regarding the EU's 2024 anti-money laundering regulatory package and the AI Act. This work was financially supported by the PID2024-160160OB-I00 project of the Spanish State Research Agency (Ministry of Science, Innovation and Universities), Operational Program FEDER